Supporting policy-making with social media and e-participation platforms data: A policy analytics framework - Simonofski, Anthony; Fink, Jerôme; Burnay, Corentin (Government information quarterly, 2021)
E-participation enables citizens to have an impact on policy-making through electronic means. Two of the most popular channels are social media and dedicated e-participation platforms. However, the ideas, comments, discussions of citizens on these two channels generate a lot of data to be processed by political representatives or public agents afterwards. Despite the existence of various techniques for social media analytics, literature is scarce regarding the analysis techniques to mine e-participation platforms as well as the possible combination of insights between the two channels. In order to address these gaps, we design a policy analytics framework to leverage insights from e-participation platforms and social media through relevant data analytics to support policy-making. In order to do so, we rely on the Design Science Research methodology. Through the analysis of four different cities in Belgium (Liège, Mons, Marche-en-Famenne, Leuven), we identify policy-makers' requirements and needs of information from platforms and social media. Then, we explore data analysis techniques to address those requirements. Finally, we design an actionable framework, present it as an interactive dashboard and iteratively test it on the case of Liège. This policy analytics framework supports each step of the traditional policy-making process with appropriate data analytics applied to the two sources. •Policy Analytics refers to the use of data analytics to support policy-making;•Data from social media and e-participation platforms are difficult to combine and process;•Policy-makers' requirements towards policy analytics are identified;•Our framework bundles data analysis techniques for the whole policy-making process;•The framework is presented and validated as a dashboard to increase usability.